KING COCONUT - Nandanie D. Ediriweera, Ph.D. (CORD, 1996)
The king coconut (Thambili) which is characterized by its bright orange colour is said to have originated in Sri Lanka and is tertned cocos nucifera var. Aurantiaca. The diagnostic characters of varieties are mostly nut size, colour of epicarp, mesocarp and thickness of endosperm.